DARI TRADISIONAL KE POST MODERN: PERKEMBANGAN HISTORIOGRAFI INDONESIA - Husna, Krida Amalia (SENTRI: Jurnal Riset Ilmiah, 2024)
History writing has changed from time to time influenced by the development of science, politic, social, and culture. Using historical methods, this paper describes the development of Indonesian historiography from traditional to post modern. From the description, it can be seen that the influence of Indonesian historiography developed through a process of response and critics. In addition, although sometimes reluctant to be acknowledged, earlier historiography often became the source and foundation for subsequent historiography